2019
DOI: 10.1002/chem.201806117
|View full text |Cite
|
Sign up to set email alerts
|

Boosting Molecular Complexity with O2: Iron‐Catalysed Oxygenation of 1‐Arylisochromans through Dehydrogenation, Csp3−O Bond Cleavage and Hydrogenolysis

Abstract: Oxidative cleavage of the Csp3−O bond in 1‐arylisochromans with stoichiometric oxidants, such as CrO3/H2SO4, has been practiced for decades in synthetic chemistry. Herein, we report that a structurally well‐defined FeII–pyridyl(bis‐imidazolidine) catalyst promotes the aerobic oxygenation of 1‐arylisochromans, affording highly selectively 2‐(hydroxyethyl)benzophenones, compounds of potential for neuroprotective agents. Key intermediates have been isolated, indicating that the reaction proceeds through dehydroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 126 publications
0
2
0
Order By: Relevance
“…Although the original PyBidine ( L2 ) was developed using N -benzyl diphenyldiamine (i.e., Bn-PyBidine), the substituent on the nitrogen atom can be changed. Among the N -substituents examined, a tosylated PyBidine (Ts-PyBidine) , was effective in improving the enantioselectivity of 3aa at up to 70% ee. Surprisingly, the other cationic first-row transition metal complexes possessed significantly greater catalytic activity (entries 7–9).…”
mentioning
confidence: 99%
“…Although the original PyBidine ( L2 ) was developed using N -benzyl diphenyldiamine (i.e., Bn-PyBidine), the substituent on the nitrogen atom can be changed. Among the N -substituents examined, a tosylated PyBidine (Ts-PyBidine) , was effective in improving the enantioselectivity of 3aa at up to 70% ee. Surprisingly, the other cationic first-row transition metal complexes possessed significantly greater catalytic activity (entries 7–9).…”
mentioning
confidence: 99%
“…Experimentally we found that the [(trans‐BPP)Mn II (OTf) 2 ] complex catalyzes efficient oxidation of 1‐arylisochromanes, affording 2‐(hydroxyethyl)benzophenones in high yields (Scheme 2). We have previously reported an iron complex that is capable of activating O 2 and catalyzes similar reactions with O 2 as the oxidant, albeit requiring a higher temperature and longer reaction time [9c] . In contrast, the structurally similar [(cis‐BPP)Mn II (OTf) 2 ] is much less active, affording a yield of <10 % in the case of 1‐phenylisochromane.…”
Section: Resultsmentioning
confidence: 99%